1800 Uk unscheduled admissions for adults with suspected seizures. (1st December 2017) - Grunewald, Richard; Dickson, Jon; Hick, Julian; Jacques, Richard; Campbell, Michael; Morley, Rebeka; Reuber, Markus; Dickson, Jon M; Hick, Julian; Jacques, Richard; Grünewald, Richard A; Campbell, Michael J; et al.
Abstract : Introduction: Suspected seizures are a common reason for admission to hospital. Rates of unscheduled admission are of interest as it may reflect the quality of local services for epilepsy. Methods: We searched the Hospital Episodes Statistics (HES) in-patient database for unscheduled/emergency NHS admissions in adults in England between 1 April 2007 – 31 March 2013, and categorised them by ICD-10 diagnosis (epilepsy/seizure/convulsion, G40, G41, R56.8). Variation in admission was analysed by funnel plots. Results: There were 8 17 030 admissions for neurological conditions during the study period (mean=1 36 171 per year). 38.9% of these were for epilepsy/seizure/convulsion, and this comprised the major neurological cause for admission (0.75% of all emergency admissions). There was geographical variability in the rate of admissions. There were peaks of rates of admission in middle and old age. Men were admitted more commonly than women. The median length of stay was 1 day. The median cost per admission was £1650 (IQR £1090 to 1856, range £0 to £217, 998) and the mean total cost per year to the NHS in England was £93 million. Conclusions: Suspected seizures are an important cause of neurological admissions to hospital. The significant geographical variability may reflect local variation in quality of care.